TINJAUAN TEORITIS MEDIA PEMBELAJARAN MATEMATIKA DENGAN APLIKASI TIKTOK - Saman Saman (Fakultas Pertanian, 2023)
Articles discuss the important role of technology in modern education with a focus on learning media such as TikTok. The VISUALS principle is used to design interesting and effective learning media. In learning mathematics, TikTok has the potential to visualize abstract concepts and creativity. Ideas for use include explaining concepts, solving problems, collaborative projects, and competitions. It is important to strike a balance between entertainment and education, as well as monitor impact, communicate with parents and ensure content is within the curriculum. In conclusion, TikTok and similar learning media can enhance learning with interesting visualizations and interactions in the technological age.